Cardiopulmonary resuscitation-associated injuries in still-/newborns, infants and toddlers in a German forensic collective. (October 2017) - Ondruschka, B.; Baier, C.; Siekmeyer, M.; Buschmann, C.; Dreßler, J.; Bernhard, M.
Highlights: No registered CPR-associated injury was declared significant or life-threatening. Skeletal or soft tissue injuries occur very rarely after pediatric CPR. A thorough evaluation for possible abuse is necessary if such injuries are diagnosed. Professionals do not need to have any fear about intensive CPR attempts in case of pediatric emergencies. Abstract: Introduction: Cardiopulmonary resuscitation (CPR) may lead to injuries. Forensic experts are sometimes confronted with claims that fatal injuries were caused by chest compressions during CPR rather than by assaults. We want to answer, how often CPR-associated injuries are present in younger children and if they may mimic injuries caused by abuse. Material and methods: All autopsy records of the Institute of Legal Medicine in Leipzig, Germany in a 6-year study period were used (2011–2016). There were 3664 forensic autopsies in total, comprising 97 autopsies of children ≤4 years. After exclusion criteria we were able to include 51 cases in the study. Following this, all CPR-related variables were collected according to the 'Utstein style'. Standard procedures were used for statistical evaluation of the data. Results: The most common cause of cardiac arrest was SIDS. The mean duration of CPR was 50 min. Bystander CPR was performed in 43.1%. In no single case death was declared without at least partly professional CPR. Most of the children were first resuscitated out-of-hospital (41.2%). 27.5% of the children had at least one CPR injury without preference to an age group. None of the recorded CPR-associated injuries were considered significant or life-threatening. The duration of CPR or presence of bystander CPR did not correlate to the presence of any detected injury. Conclusion: Skeletal injuries and relevant injuries to the soft tissue and organs seem to occur only very rarely after pediatric CPR. Whenever such injuries are diagnosed, the children should be examined thoroughly for potential abuse.